2022
DOI: 10.3390/s22051775
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Wavebands Selection for the Detection of Potential Foreign Materials in Fresh-Cut Vegetables

Abstract: Ensuring the quality of fresh-cut vegetables is the greatest challenge for the food industry and is equally as important to consumers (and their health). Several investigations have proven the necessity of advanced technology for detecting foreign materials (FMs) in fresh-cut vegetables. In this study, the possibility of using near infrared spectral analysis as a potential technique was investigated to identify various types of FMs in seven common fresh-cut vegetables by selecting important wavebands. Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Compared with other foods, there are few reports about the application of imaging technology for foreign body detection in fresh cutting processing, only focusing on HSI and FI. Tunny et al (2022) evaluated the feasibility of multispectral NIR imaging for the detection of various foreign bodies (including paper, plastic, rubber, wood, stone, insects, nail, etc.; Figure 4a) in seven fresh-cut vegetables (zucchini, potato, onion, green onion, radish, carrot, and cabbage). The results showed that the foreign body detection accuracy of 7 fresh-cut vegetables using 6 different band combinations (1150, 1400, 1450, 1731, 1880, and 1920 nm) was 92.5%.…”
Section: Impurity/foreign Bodies Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other foods, there are few reports about the application of imaging technology for foreign body detection in fresh cutting processing, only focusing on HSI and FI. Tunny et al (2022) evaluated the feasibility of multispectral NIR imaging for the detection of various foreign bodies (including paper, plastic, rubber, wood, stone, insects, nail, etc.; Figure 4a) in seven fresh-cut vegetables (zucchini, potato, onion, green onion, radish, carrot, and cabbage). The results showed that the foreign body detection accuracy of 7 fresh-cut vegetables using 6 different band combinations (1150, 1400, 1450, 1731, 1880, and 1920 nm) was 92.5%.…”
Section: Impurity/foreign Bodies Detectionmentioning
confidence: 99%
“…Foreign body diagram (Tunny et al., 2022) (a); Schematic diagram of fluorescence imaging instrument (b); Fluorescence classification image of foreign body mixed with cabbage and green onion (Lohumi et al., 2021) (c); Fluorescence imaging results of foreign body detection in zucchini and green onion, as well as the reflectance imaging results of foreign body detection in garlic, carrot and onion (Cho, 2021) (d)…”
Section: Application Of Various Imaging Technologies In Fresh‐cutting...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, using this stack of wavelength images or spectral cube, the average intensity and local changes of the intensity pixels at each spectral image may be analyzed and used for pattern identification. However, expensive and specialized hardware is required to capture hyperspectral images (Nakawajana et al 2021;Tunny et al 2022). In general, hyperspectrometers with somewhat higher resolution cost over a million dollars.…”
Section: Introductionmentioning
confidence: 99%
“…Further, food safety deals with the safety of the food production line, ranging from on-farm to off-farm practices [7,8]. Hazards commonly occur due to chemical contamination [9], physical contamination [10,11], food adulteration [12,13], genetic modification [14], and other processes. Chemical contamination and food adulteration in agricultural products are present as the side effects of food unavailability.…”
Section: Introductionmentioning
confidence: 99%